Applied sociolinguistics : an empirical study - Singh, Irom Gambhir (New Delhi : Akansha Pub. House, 2010)
Study on socio-pedagogic perspectives on the power and politics of English in Assam and Manipur states of North-east India.
Includes bibliographical references (p. [148]-170) and index.
Keywords: English language -- Social aspects -- India -- Assam; English language -- Social aspects -- India -- Manipur; Sociolinguistics -- India -- Manipur; Sociolinguistics -- India -- Assam